2012
DOI: 10.3390/ma5112353
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube Electron Emitter for X-ray Imaging

Abstract: The carbon nanotube field emitter array was grown on silicon substrate through a resist-assisted patterning (RAP) process. The shape of the carbon nanotube array is elliptical with 2.0 × 0.5 mm2 for an isotropic focal spot size at anode target. The field emission properties with triode electrodes show a gate turn-on field of 3 V/µm at an anode emission current of 0.1 mA. The author demonstrated the X-ray source with triode electrode structure utilizing the carbon nanotube emitter, and the transmitted X-ray ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 12 publications
(15 reference statements)
0
20
0
Order By: Relevance
“…In addition, they demonstrated peak pulse currents of up to 28 mA (emitted area not stipulated), without vacuum breakdown, at an anode potential of 14 kV. Using CVD grown CNT arrays, Ryu et al [205] reported emission currents of up to 90 mA (emitted area not stipulated) in a diode configuration, although in a gate-controlled triode arrangement, the beam currents were substantially reduced.…”
Section: High Beam Currentmentioning
confidence: 95%
See 4 more Smart Citations
“…In addition, they demonstrated peak pulse currents of up to 28 mA (emitted area not stipulated), without vacuum breakdown, at an anode potential of 14 kV. Using CVD grown CNT arrays, Ryu et al [205] reported emission currents of up to 90 mA (emitted area not stipulated) in a diode configuration, although in a gate-controlled triode arrangement, the beam currents were substantially reduced.…”
Section: High Beam Currentmentioning
confidence: 95%
“…A resist-assisted patterning process was used to produce a cathode assembly consisting of a gate and focusing electrode. This assembly was approximately 0.5 mm × 2.0 mm and gave an isotropic focal spot [205]. Ryu et al also described a further shaping technique for post processing the as-grown vertically aligned CNTs.…”
Section: Beam Profilingmentioning
confidence: 98%
See 3 more Smart Citations